The Centration Dilemma in Refractive Corrections: Why Is It Still a Dilemma and How to Cope? - Samuel Arba Mosquera; Shwetabh Verma (Photonics)
(1) Background: Defining the optimum center for laser refractive corrections is difficult, with many of the available approaches having pros and cons. Decentered ablations result in undesirable side effects like halos, glare, monocular diplopia, and a reduction in visual acuity; (2) Methods: The ideal centration in refractive corrections should fulfil three requirements: covering a scotopic pupil; respecting the visual axis; and minimizing tissue removal. The implications of different centration strategies are discussed and shown graphically; (3) Results: Oversized asymmetric offset ablation faces fewer difficulties in registering static cyclotorsion, features less tissue wastage compared to a symmetric offset, and includes a certain amount of coma (and trefoil) in the profile, benefiting eyes with a pupil offset, which typically present with relevant amounts of coma and trefoil corneal aberrations due to decentered optics; (4) Conclusions: There is a need for a flexible choice of centration in refractive procedures to design customized and non-customized treatments optimally. An ideal optical zone covering the pupil with the widest entrance may be as important as a centration reference.